2020
DOI: 10.1186/s12954-020-00416-w
|View full text |Cite|
|
Sign up to set email alerts
|

Hostility, compassion and role reversal in West Virginia’s long opioid overdose emergency

Abstract: Background West Virginia is a largely rural state with strong ties of kinship, mutual systems of support and charitable giving. At the same time, wealth inequalities are extreme and the state’s drug overdose fatality rate stands above all others in the USA at 51.5/100,000 in 2018, largely opioid-related. In recent years, harm reduction services have been active in the state but in 2018 Charleston’s needle and syringe program was forced to close. This paper considers the risk environment in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 51 publications
(74 reference statements)
0
25
0
Order By: Relevance
“…Finally, the COVID-19 pandemic has been associated with increased opioid overdoses ( Ali et al, 2021 , Slavova et al, 2020 , Special Advisory Committee on the Epidemic of Opioid Overdoses, 2021 ), and decreased access to harm-reduction services ( Whitfield et al, 2020 ). Despite a number of brief communications on the converging public health crises of the opioid overdose epidemic and COVID-19 (see for example Alexander et al (2020) , Dunlop et al (2020) and Khatri and Perrone (2020) ), we did not identify any published evidence on the impact of the pandemic on the prevalence of opioid use or opioid use disorder at the population level.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, the COVID-19 pandemic has been associated with increased opioid overdoses ( Ali et al, 2021 , Slavova et al, 2020 , Special Advisory Committee on the Epidemic of Opioid Overdoses, 2021 ), and decreased access to harm-reduction services ( Whitfield et al, 2020 ). Despite a number of brief communications on the converging public health crises of the opioid overdose epidemic and COVID-19 (see for example Alexander et al (2020) , Dunlop et al (2020) and Khatri and Perrone (2020) ), we did not identify any published evidence on the impact of the pandemic on the prevalence of opioid use or opioid use disorder at the population level.…”
Section: Discussionmentioning
confidence: 90%
“…Early in the outbreak, high rates of moderate or severe psychological impact as a result of COVID-19 were reported in China ( Wang et al, 2020 ). Within the general context of mental health concerns, it is critical to bring attention to substance use (SU) and substance use disorders (SUD) given their associated global disease burden ( Degenhardt et al, 2018 ) as well as the unique challenges that a pandemic may present for those using substances and the services they require ( Dunlop et al, 2020 , Ornell et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although compassion and stigma are not opposing poles on a single continuum, these constructs tend to be at odds by definition and based on existing substance use research. 31 , 32 , 33 Future studies of emergency personnel should examine the association between compassion and stigma with respect to substance use, including potential root causes of individual and collective views and possible explanations for changes in each construct over time at levels ranging from individual to societal.…”
Section: Discussionmentioning
confidence: 99%
“…After publication of the original article [ 1 ], the authors identified an error in Acknowledgements section. The below disclosures is missing.…”
Section: Correction To: Harm Reduct J (2020) 17:74 101186/s12954-020-00416-wmentioning
confidence: 99%